Childhood Maltreatment Experience Influences Neural Response to Psychosocial Stress in Adults: An fMRI Study - Zhong, Xue; Ming, Qingsen; Dong, Daifeng; Sun, Xiaoqiang; Cheng, Chang; Xiong, Ge; Li, Chuting; Zhang, Xiaocui; Yao, Shuqiao (Frontiers in Psychology, 2020)
Background: Childhood maltreatment is a strong risk factor for the development of depression in later life. However, the neurobiological mechanisms underlying this vulnerability are not well understood. As depression has been associated with dysfunction of the HPA axis and increased responsiveness to psychosocial stressors, we speculated that childhood maltreatment may lead to lasting alteration of the stress response system, thereby increasing the risk of depression. This study investigated the effects of childhood maltreatment on the stress response in healthy subjects while controlling for psychiatric condition. Methods: Forty-eight healthy young adults (24 females) with childhood maltreatment experience and 48 healthy controls (33 females) without such experience were administered the Montreal Imaging Stress Task during functional magnetic resonance imaging. Childhood maltreatment experience was assessed using the 28-item Childhood Trauma Questionnaire. Between-group differences in subjective stress levels, whole brain activations and cortisol levels were assessed. Results: Relative to healthy control subjects, individuals exposed to childhood maltreatment exhibited higher subjective stress and cortisol levels. Neurofunctionally, participants with histories of childhood maltreatment displayed significantly increased activation in the dorsolateral prefrontal cortex, insula and precuneus, and decreased activation in ventromedial prefrontal cortex relative to healthy controls during the psychosocial stress task. Activations in dorsolateral prefrontal cortex and insula correlated with CTQ scores in the childhood maltreatment group. Conclusions: The results of this study show that childhood maltreatment induces lasting changes in brain function and HPA-axis responsiveness to stress. The observed abnormal activation in the dorsolateral prefrontal cortex, insula and ventromedial prefrontal cortex and enhanced cortisol response are similar to those seen in individuals with depression. This dysfunction might serve as a diathesis that embeds latent vulnerability to psychiatric disorders, and this mechanism provides evidence supporting the stress sensitization model.